Design of an assistive device to detect freezing episodes and provide audio/vibratory cues to avoid falls - Chowdhury, Vivek; Goswami, Arka; Nigam, Rakshit; A Sridhar, P (International Journal of Engineering and Technology, 2018)
This paper primarily discusses the Freezing of Gait which is a type of gait abnormality and generally occurs in Parkinson Disease patients which cause an interruption to their life. During a FOG episode, the subject is rendered unable to continue moving or even manoeuver. These episodes give rise to the danger of the patient landing on the ground and often renders a person immobile. The aim of this device is to develop a technique to identify the effect of ‘Freezing of Gait’ in people suffering from Parkinsons Disease and to provide feedback on detection and improving self-efficiency in about their daily life.
Keywords: .